Hubungan Antara Perubahan Fisik Dengan Perubahan Psikologis Wanita Pada Masa Menopause Di Kelurahan Pucang Sawit Kecamatan Jebres - Indrias, Hesty Destia, Arina Maliya, S.Kep., M.Si.Med, Rina Ambar wati, S.Kep., Ns (2015)
A menopausa woman who will begin reduce of health physically. Increased weight gain, hair loss, low vision are examples of physical changes. Physical changes can affect psychological conditions like menopausa women experience anxiety, fear of his own life and others. The purpose of the study is to know the relationship between physical changes with influence psychological of women during menopause in Kelurahan Pucang Sawit of Jebres. The research is descriptive analytic study with correlative design. Sample were 66 women 48-55 year old. Taking sampling used promotional random sampling. Instrument research used a physical changes questionnaire and influence of a psychological after validity and reliability test. Data analysis used chi square test . The results of research that 39 respondents ( 59.1 % ) with physical changes while 27 respondents (40.9 %) unchanged physical. 13 respondents ( 19.7 % ) changed of psychological strong level , 29 respondents ( 43,9 %) with fair category, and 24 respondents (36,4%) with low changes psychologically. The results of chi square test with X2 = 6.624 p = 0,036 so concluded there was relationship between physical changes with influence psychological of women during menopause in Kelurahan Pucang Sawit of Jebres.